FAKTOR-FAKTOR YANG MEMPENGARUHI PEMANFAATAN ATAS ADOPSI PELAYANAN E-GOVERNMENT DI INDONESIA: PERANAN INTENTION TO USE - Ayu Aldawiyyah (2023)
E-government is a complete system that connects citizens, companies, and governments around the world that will allow quick and easy access to government services. E-government applications in public operations are thought to be capable of increasing information transparency and public participation in the government administration system. There is, however, still inequality and not optimal implementation of e-government services. This must be a source of concern for the government because if it is not addressed, the people will be unable to obtain full information and services. The purpose of this study is to test the effect of trust in e-government, perceived ease of use, internet experience, performance expectancy, facilitating conditions through intention to use as mediation variable. The sample in this study was 515 Indonesian citizens obtained from the distribution of questionnaires. The data obtained were analyzed using the PLS Structural Equation Model (SEM) version 3. The results showed that trust in e-government, perceived ease of use, internet experience, performance expectancy, facilitating conditions significantly influence the intention to use e-government services and intention to use has an influence on the utilization of service adoption of e-government services.